(untitled) (Acta Education, 2024)
This article examines the importance of social philosophy in the context of the formation of value guidelines in the educational environment. Based on modern theories of social philosophy and pedagogy, as well as on empirical research presented in modern literature, the author analyzes the influence of social philosophy on the process of forming students’ values and creating a favorable educational environment. The author pays special attention to the proposed recommendations in their relationship with the educational process.